Multi-omics-based investigation of Bifidobacterium’s inhibitory effect on glioma: regulation of tumor and gut microbiota, and MEK/ERK cascade - Fan, Huali; Wang, Yuhan; Han, Mingyu; Wang, Li; Li, Xue; Kuang, Xi; Du, Junrong; Peng, Fu (Frontiers in Microbiology, 2024)
Glioma, the most prevalent primary tumor of the central nervous system, is characterized by a poor prognosis and a high recurrence rate. The interplay between microbes, such as gut and tumor microbiota, and the host has underscored the significant impact of microorganisms on disease progression. Bifidobacterium, a beneficial bacterial strain found in the human and animal intestines, exhibits inhibitory effects against various diseases. However, the existing body of evidence pertaining to the influence of Bifidobacterium on glioma remains insufficient. Here, we found that Bifidobacterium reduces tumor volume and prolongs survival time in an orthotopic mouse model of glioma. Experiments elucidated that Bifidobacterium suppresses the MEK/ERK cascade. Additionally, we noted an increase in the α-diversity of the tumor microbiota, along with an augmented relative abundance of Bifidobacterium in the gut microbiota. This rise in Bifidobacterium levels within the intestine may be attributed to a concurrent increase in Bifidobacterium within the glioma. Additionally, Bifidobacterium induced alterations in serum metabolites, particularly those comprised of organonitrogen compounds. Thus, our findings showed that Bifidobacterium can suppress glioma growth by inhibiting the MEK/ERK cascade and regulating tumor, and gut microbiota, and serum metabolites in mice, indicating the promising therapeutic prospects of Bifidobacterium against glioma.